The Cyclicality of Fiscal Policies in the CEMAC Region - Mpatswe, Gaston; Tapsoba, Sampawende; York, Robert (Washington, D.C. : International Monetary Fund, 2011)
This paper examines fiscal cyclicality in the CEMAC region during 1980-2008. The issue has attracted very little empirical interest but is important if fiscal policies are to play a role in mitigating external shocks that exacerbate economic cycles across the region. We assess whether fiscal policies across these six countries have been procyclical using panel data to elaborate our analysis. Like in other sub-Saharan countries, total public expenditure in the CEMAC is found to be strongly procyclical. This is most pronounced for public investment, which overreacts to output growth with elasticity above 1. We further find that institutional weaknesses and poor governance partly explain this behavior. In contrast, the existence of an IMF-supported program can be a counterbalancing influence in attenuating this bias.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet